2023
DOI: 10.1097/md.0000000000033645
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and influencing factors of infectious diarrhea in preschool children: An observational study

Abstract: Infectious diarrhea is a common disease in preschool children, but the pathogenic species, origins, and influencing factors remain debatable. Therefore, more studies are required to solve these debatable topics. A number of 260 eligible preschool children diagnosed with infectious diarrhea in our hospital were enrolled in the infection group. Meanwhile, a number of 260 matched healthy children from the health center were enrolled in the control group. The pathogenic species and origins, the time of onset of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Among virus-positive specimens, rotavirus exhibited the highest positive detection rate, followed by norovirus, astrovirus, and adenovirus ( Figure 3 ). The predominance of rotavirus aligns with global trends, as it is widely acknowledged as one of the leading causes of severe gastroenteritis in children worldwide ( 25 ). This highlights the prevalence and burden of rotavirus and underscores the importance of continued efforts to prevent, diagnose and treatment of rotavirus diarrheal disease.…”
Section: Discussionmentioning
confidence: 80%
“…Among virus-positive specimens, rotavirus exhibited the highest positive detection rate, followed by norovirus, astrovirus, and adenovirus ( Figure 3 ). The predominance of rotavirus aligns with global trends, as it is widely acknowledged as one of the leading causes of severe gastroenteritis in children worldwide ( 25 ). This highlights the prevalence and burden of rotavirus and underscores the importance of continued efforts to prevent, diagnose and treatment of rotavirus diarrheal disease.…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, human enteroviruses, including sapoviruses, noroviruses and astroviruses, were detected from cockroaches in food-related environments, which were also found in human diarrhoeal disease surveillance. Research found that the common pathogens of infectious diarrhea in children include salmonella, rotavirus, shigella, vibrio, and norovirus 47 . The types of viruses detected in the above study are similar to those in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, human enteroviruses, including sapoviruses, noroviruses and astroviruses, were detected from cockroaches in Food-Related Environments, which were also found in human diarrhoeal disease surveillance. Studies have found that the common pathogens of infectious diarrhea in children are salmonella, rotavirus, shigella, vibrio, and norovirus 43 . The types of viruses detected in the above study are similar to those in this study.…”
Section: Discussionmentioning
confidence: 99%